Association of professional identity, job satisfaction and burnout with turnover intention among general practitioners in China: evidence from a national survey - Tao Zhang; Jing Feng; Heng Jiang; Xin Shen; Bo Pu; Yong Gan (BMC, 2021)
Abstract Background The complex interrelationships between professional identity, job satisfaction, burnout, and turnover intention among general practitioners (GPs) are insufficiently understood in China. This study aimed to investigate the interrelationships between professional identity, job satisfaction, burnout, and turnover intention in China, and to examine whether job satisfaction and burnout played mediating roles between professional identity and turnover intention. Methods A cross-sectional survey was conducted between October, 2017 and February, 2018 in China. The participants were selected using a multistage stratified random sampling method. Data were collected with a self-administered questionnaire from 3236 GPs (response rate, 99.8%) working in community health institutions in China. Professional identity was measured by the 13 items scale, and job satisfaction scale with an 11-item designed by Shi et al. was employed. Burnout was measured using a 22-item Maslach Burnout Inventory-Human Services Survey, and turnover intention was measured with a 6 items scale. Descriptive statistics were calculated and groups' differences were estimated Student's t-test and analyses of variance. Pearson's correlation analysis was used to assess the degree of correlation among different dimensions of professional identity, job satisfaction, burnout, and turnover intention. Structural equation modeling analysis was applied to examine the interrelationships among these study variables based on the hypothesized model. Results The proposed model achieved a good model fit. Job satisfaction had a direct negative effect on turnover intention (β = − 0.38, P < 0.001), burnout had a direct positive effect on turnover intention (β = 0.37, P < 0.001), and professional identity had an indirect negative effect on turnover intention through the mediating effect of job satisfaction and burnout. Conclusions Our study elucidated the pathways linking professional identity, job satisfaction, and burnout to turnover intention of GPs. This revealed that turnover intention was significantly affected by job satisfaction and burnout, and the effects of professional identity on turnover intention can be mediated by job satisfaction and burnout.